Biodegradation of gelatin stabilized tetragonal zirconia synthesized by microwave assisted sol-gel method. (March 2022) - Bashir, Mahwish; Majid, Farzana; Akram, Summeya; Ali, Adnan; Abdelmohsen, Shaimaa A.M.
Abstract: The purpose of current work of is to organize stabilized tetragonal zirconia (t-ZrO2 ) nano-particles with microwave abetted sol-gel technique. To increase the stability and shrink the crystal size, both microwave (MW) and gelatin components are used as structure guiding methods. Gelatin was used with the aim of bone implantations, as raw materials used in gelatin production are cattle bones. It contains purified collagen protein (a main protein that in the extracellular matrix found in the body's various connective tissues) that also helps in implantations and repairing. Moreover, MW heating provides a uniform heating and control of microstructures. Zirconium oxychloride was used as precursor of zirconium Effect of gelatin contents (1g, 2g, 3g, 4g and 5g) was observed. X-ray diffraction (XRD) analysis attributes the presence of phase pure t-ZrO2 at low gelatin content 3g with crystallite size ∼6.68296 nm. Formation of phase pure t-ZrO2 without post heat treatment is due to sufficient amount of gelatin to coat the zirconia crystals. Relatively higher x-ray density has been observed in case of phase pure t-ZrO2 at 5g of gelatin content. Value of the hardness is increasing from 1263 to 1443 HV with gelatin content due to phase strengthening. Raman shift presents characteristic peak at 148 cm −1 of tetragonal zirconia. Phase fraction calculated from Raman spectra is in good agreement with XRD data. At 3g of gelatin content porous structure has been observed in scanning electron microscope images. This porosity decreases with gelatin content and the distribution of particles is more uniform, and dispersion is better. The porosity of the samples decreases and reaching a minimum value at 5g of gelatin content, at which the sample was the densest. The size of nanoparticles is in the range of 500–600 nm. Optimized t-ZrO2 is soaked in stimulated body fluid (SBF) for 1, 2, 4, 8, 12, 18 and 24 weeks. Slight variation in weight and hardness has been observed even after 24 weeks of soaking.